ANALISIS CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE SEBAGAI PERWUJUDAN GREEN ACCOUNTING (Studi Pada Perusahaan Dengan Peringkat Emas, Hijau dan Biru Berdasarkan Data PROPER) - Puspita, Dyah Aruning; Murtiningtyas, Triana (DINAMIKA DOTCOM, 2014)
The purpose of this study was to determine the extent to which companies that have the gold, green and blue in a report based on data PROPER activities undertaken as a manifestation of CSR in their annual reports (both financial and non-financial). In addition, to determine the application of CSR reporting costs incurred by companies rated gold, green and blue that reflects green accounting. Researchers took a sample twentieth firms from data released by the PROPER. Because this program is intended to encourage companies to adhere to environmental regulations through the principles of sustainable development in the process of production and services with an environmental management system, 3R, energy efficiency, resource conservation da ethical business conduct and responsibility toward society. Green accounting is an accounting environment describes an attempt to combine the environmental benefits and costs into economic decision making. The results showed thatÂ  the twentieth companies were sampled in the study based on data reported PROPER still quite diverse social activities. Some are included in the notes to the financial statements are included in general and administrative expenses and reporting into the account "repairs and maintenance" account "other" account or log in "public relations" But there is also considerable detail in the reporting of social activities and environment in each assessment component PROPER explanation. Still reporting version of the diversity of their respective companies strongly agree with the author of previous researchers that the importance of efforts to improve the implementation of environmental accounting in which the involvement of the Indonesian Institute of Accountants (IAI) to develop guidelines for Sustainability Reporting and requires the application of existing reporting guidelines so that the objectives of the Green Accounting will be realized.Â Keywords: Corporate Social Responsibility (CSR), Sustainability Report, Green Accounting